Can bupivacaine applied intraoperatively into paravertebral muscle tissues reduce the need for postoperative narcotic analgesics and/or nonsteroids? (Annals of Medical Research, 2022)
Aim: Although the length of hospital stay after lumbar microdiscectomy operations, one of the most common surgical interventions in current neurosurgery practice, is quite short, nausea-vomiting and urinary retention, particularly postoperative pain, may prolong this period. Also, systemic side effects may occur in cases due to pharmacological agents applied for postoperative pain control. This study was conducted to seek answers to whether bupivacaine administered intraoperatively into the paravertebral muscle mass decrease the need for postoperative narcotic analgesics and/or nonsteroidal anti-inflammatory drugs (NSAIDs).Materials and Methods:  Lumbar disc hernia patients with a similar history of age, gender, body weight, disc hernia level, preoperative pain score, and preoperative analgesic use were included in the study between 01.06.2020 and 31.06.2021 (n=48). The control group of the study consisted of cases who did not receive paravertebral intramuscular bupivacaine during single-level lumbar microdiscectomy operations under general anesthesia and named as group 1 (n=24). The study group of the study consisted of cases who were administered preoperative paravertebral intramuscular bupivacaine and named group 2 (n=24). After the operation, the assessment of pain with the frequency of need for morphine sulfate or pethidine hydrochloride was performed with the Visual Analogue Scale (VAS). After the obtained data were assessed with a one-way analysis of variance, the relationship between parameters was tested using the Pearson correlation coefficient (r). Alpha significance value was accepted as
Keywords: Bupivacaine; Dexketoprofen trometamol; Lumbar microdiscectomy; Morphine sulfate; Pethidine hydrochloride; Postoperative pain